2008
DOI: 10.1016/j.immuni.2008.10.008
|View full text |Cite
|
Sign up to set email alerts
|

PlexinD1 Glycoprotein Controls Migration of Positively Selected Thymocytes into the Medulla

Abstract: Summary Precise intrathymic cell migration is important for thymocyte maturation and architecture. The orchestration of thymocyte trafficking, however, is not well understood at a molecular level. Here, we describe highly-regulated plexinD1 expression on CD4+CD8+ double positive (DP) thymocytes which is further affected by T cell receptor/co-receptor engagement. Activation of plexinD1 via one of its ligands, semaphorin3E, represses CCR9/CCL25 signaling in CD69+ thymocytes. In the absence of plexinD1, CD69+ thy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
153
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 117 publications
(160 citation statements)
references
References 41 publications
7
153
0
Order By: Relevance
“…47). In particular, Sema3E and PlexinD1 have been reported to play an active role in vascular system development 29,48,49 , but they also control the migration of mouse thymocytes 50 and tumour cells 51 . Indeed, mice lacking Plxnd1 showed impaired thymocyte trafficking 50 and a poorly developed vascular system 29 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…47). In particular, Sema3E and PlexinD1 have been reported to play an active role in vascular system development 29,48,49 , but they also control the migration of mouse thymocytes 50 and tumour cells 51 . Indeed, mice lacking Plxnd1 showed impaired thymocyte trafficking 50 and a poorly developed vascular system 29 .…”
Section: Discussionmentioning
confidence: 99%
“…In particular, Sema3E and PlexinD1 have been reported to play an active role in vascular system development 29,48,49 , but they also control the migration of mouse thymocytes 50 and tumour cells 51 . Indeed, mice lacking Plxnd1 showed impaired thymocyte trafficking 50 and a poorly developed vascular system 29 . Today, it is generally accepted that the stereotypical organization of the blood vessels is guided by the same genetic and molecular mechanisms that guide developing axons (reviewed in refs 26,36), although it is only in recent years that the developmental role played by Sema3E/PlexinD1 in the central and peripheral nervous systems began to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…81 In addition, it has been shown that some chemorepellent molecules, including semaphorins and ephrins, affect thymocyte differentiation during their development. [82][83][84] Sema3E, which interacts with plexin-D1 in an NP-1-independent manner, was recently reported to participate in thymocyte development. 82 Plexin-D1 expression is high in CD4 1 CD8 1 thymocytes (double-positive, DP) but decreased in single-positive cells.…”
Section: Semaphorins In the Thymusmentioning
confidence: 99%
“…[82][83][84] Sema3E, which interacts with plexin-D1 in an NP-1-independent manner, was recently reported to participate in thymocyte development. 82 Plexin-D1 expression is high in CD4 1 CD8 1 thymocytes (double-positive, DP) but decreased in single-positive cells. Furthermore, its ligand, Sema3E, is preferentially expressed in the medulla rather than in the cortex.…”
Section: Semaphorins In the Thymusmentioning
confidence: 99%
“…While studying the molecular interactions controlling mouse thymocyte development, we identified plexinD1 as a critical mediator for thymocytes destined to mature into T lymphocytes populating the mammalian immune system (6). Plxnd1 encoding plexinD1 is transcriptionally regulated at a key intermediate stage of thymocyte development.…”
mentioning
confidence: 99%